2019
DOI: 10.1177/1559827619836676
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Lifestyle Medicine Curriculum in Undergraduate Medical Education

Abstract: While scientific evidence demonstrates conclusive associations between unhealthy lifestyle behaviors and increased morbidity and mortality related to noncommunicable chronic diseases (NCDs), most physicians are not formally taught the root causes of NCDs nor how to counsel patients regarding their lifestyle behaviors for disease prevention and treatment. Since its inception in 2012, the University of South Carolina School of Medicine Greenville has designed, developed, and implemented an innovative, formalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It is important that these programs and opportunities are evaluated, with outcomes addressing the reaction, learning, behaviour, and results levels [ 55 ]. Embedding such additional training within university programs has the potential to improve their dietary and exercise management skills and confidence levels that can positively impact patient health outcomes [ 56 – 58 ]. Ideally, resources should include clear information on specific dietitians and exercise professionals who can provide proper assessment, programming, and support; and information on referral pathways to reach these specialists or community services [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that these programs and opportunities are evaluated, with outcomes addressing the reaction, learning, behaviour, and results levels [ 55 ]. Embedding such additional training within university programs has the potential to improve their dietary and exercise management skills and confidence levels that can positively impact patient health outcomes [ 56 – 58 ]. Ideally, resources should include clear information on specific dietitians and exercise professionals who can provide proper assessment, programming, and support; and information on referral pathways to reach these specialists or community services [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, resources should include clear information on specific dietitians and exercise professionals who can provide proper assessment, programming, and support; and information on referral pathways to reach these specialists or community services [ 42 ]. However, significant barriers to undertaking CPD and training at universities exist, including a lack of time, understaffing, competition for time in the existing curriculum, and perceived importance at the faculty level in universities [ 58 , 59 ]…”
Section: Discussionmentioning
confidence: 99%
“…In one study in the USA [ 7 ], fewer than 50% of primary care physicians routinely provided patients with specific guidance on nutrition, exercise, or weight control. Physicians reported that barriers to providing counseling on lifestyle behavioral change include insufficient confidence, lack of knowledge and skills, and lack of time, compensation and resources [ 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite recognition of its importance by the AMA and the American College of Lifestyle Medicine (ACLM), there remains inadequate lifestyle medicine training across the medical education continuum [ 15 ]. Multiple reports from physicians, residents, and medical students show the gaping void in LM training and education [ 10 ]. In 1985, the National Academy of Sciences recommended that 25-hours should be dedicated to nutrition [ 16 ] yet by 2010, only 27% of US medical schools had incorporated nutrition courses into their curricula [ 17 ] and very minimal physical activity promotion is taught [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The University of South Carolina School of Medicine Greenville is a pace-setting institution that has integrated approximately 86 hours of nutrition, exercise, sleep, and behavior change education through a formalized lifestyle medicine curriculum incorporated throughout all 4 years of undergraduate medical education. 10 Other examples include the Western University of Health Sciences College of Osteopathic Medicine of the Pacific and the Loma Linda University Health Preventive Medicine and Family Medicine residency programs, which offer lifestyle medicine tracks and concentrations. 9 Progressive institutions like these are helping students and residents comprehend, at an earlier time in their careers, the value of why diet and lifestyle are among the first-line therapies for the prevention and treatment of lifestyle-related chronic diseases, many of which are the leading causes of death in the United States.…”
mentioning
confidence: 99%